2001
DOI: 10.1093/intqhc/13.5.409
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and perceptions of Greek patients regarding the quality of dental health care

Abstract: Expectations and demands regarding empathy (approach to the patient) and assurance were placed at the top of the patients' priorities. A highly significant quality gap was observed between the desires of the patients and their perceptions (P< 0.01) and the largest gap was noted concerning information they received about oral health diseases. The largest quality gap was also observed in characteristics regarding responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 10 publications
8
74
1
3
Order By: Relevance
“…The result of Karydis et al (2001) in physical dimension are opposite to results of the study; results from Costas and Vasiliki (2008) are also inconsistent with the result of this study. According to the results of this study, there is a gap between the existing situation and the desired situation in physical dimensions of SERVQUAL (-0.718); in responsiveness (-1.916), in empathy (-1.039), in reliability (-1.015), and also in the assurance dimension (-1.701).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The result of Karydis et al (2001) in physical dimension are opposite to results of the study; results from Costas and Vasiliki (2008) are also inconsistent with the result of this study. According to the results of this study, there is a gap between the existing situation and the desired situation in physical dimensions of SERVQUAL (-0.718); in responsiveness (-1.916), in empathy (-1.039), in reliability (-1.015), and also in the assurance dimension (-1.701).…”
Section: Discussioncontrasting
confidence: 99%
“…Stakeholders of higher education consist of students, staff, science committee, industry and society; students have attracted the most attention, because their unmet expectations are key factors in rejecting mentioned institutions (Fitri et al, 2008). The first essential step in improving service quality is knowing the customers' perceptions and expectations of service quality and determining the service quality gap, then adopting required strategies to reduce the gap and ensuring their perspectives are realized (Karydis et al, 2001). Continuous improvement in the quality of science, university and higher education as one of the main challenges of the competitive world in the age of information and knowledge economy requires endogenous development of evaluation culture (Ferasatkhah, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to Kulich et al, empathetic communication appears to be a particularly important, but under-provisioned in dental education. 12 In the present study, three batches of students (3 rd , final, interns) were considered because these students come in contact with patients which is contrary to the study by A. Beattie 2 where only first year students were part of study. In this study, the mean empathy score was more in the age group of 21-22 years (70.54) and for males (70.95) where as the mean score was 61.88 in pre-course in A. Beattie study but there was no statistical significant difference found.…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies of perceptions and expectations of dental care, this study shows the importance of effective and sympathetic dentist-patient communication within emergency or out-of-hours consultations. [30][31][32] It also implies that Although relief from pain, and specific treatments expected to obtain it, dominate patient expectations, their wants and expectations were not solely based on symptoms and treatments. For a considerable number of patients ending uncertainty about the cause of their problem was at least as important as relief from immediate symptoms.…”
Section: 'Yeah Stop the Pain I Think Yeah I Don't Know If I Need Anmentioning
confidence: 99%